Effects of compost and defatted oilseed meals as sustainable organic fertilisers on cardoon (Cynara cardunculus L.) production in the Mediterranean basin. Issue 5 (3rd September 2019) - Ronga, Domenico; Villecco, Domenica; Zaccardelli, Massimo
ABSTRACT: Cardoon ( Cynara cardunculus L.) is considered as one of the most suitable energy crops for Southern Europe. The aim of this work was to outline the effects of organic fertilisers on the productivity and the global warming potential (GWP) on cardoon production. Six fertilisers (N 100 kg ha −1, N 50 kg ha −1, Compost 30 t ha −1, Compost 15 t ha −1  + N 25 kg ha −1, 3 t ha −1 of defatted oilseed meals of sunflower, 3 t ha −1 of defatted oilseed meals of Brassica carinata ), and unfertilised control, were evaluated on two cultivars ('Gobbo di Nizza' and 'Altilis 41') in a split-plot experiment. Defatted oilseed meal of sunflower recorded higher total dry weight (+10%), seed yield (+17%), nitrogen use efficiency (+14%) and better GWP (−66%) compared to the other organic fertilisers and performing as well as N 100 kg ha −1 . Altilis 41 cultivar showed the highest aboveground total dry weight (10 t ha −1 y −1 ), seed yield (1.7 t ha −1 y −1 ), stalk dry weight (7 t ha −1 y −1 ) and head dry weight (3 t ha −1 y −1 ). Our results highlighted that by combining suitable cultivar and fertilisation strategies, it could be possible to increase the production sustainability of C. cardunculus .